The Relative Importance of Work as a Factor in Life Satisfaction - White, Terrence (Relations industrielles / Industrial Relations, 1981)
This study assesses the impacts of job satisfaction on life satisfaction through the analyses of data obtained from a sample of respondents who held full-time employment.